POTENSI PEMBERIAN SEL PUNCA MESENKIMAL (Mesenchymal Stem Cells) SEBAGAI TERAPI IMUNOMODULATOR PADA PERBAIKAN PARU PASIEN PNEUMONIA COVID-19: Systematic Review - Andi Salsabilah (2020)
Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) is a new type of a positive and single-stranded RNA virus and originates from the genus Coronaviridae. On March 11, 2020, WHO declared the SARS-CoV-2 epidemic virus to become a pandemic due to an increase in cases of 126,063 positive people, 67,071 recoveries, and 4,616 deaths. Until now, there has been no specific treatment, such as antivirals or vaccines for COVID-19 patients, so there is a need for innovative therapeutic strategies to treat COVID-19 patients, one of which is by presenting stem cell therapy based on Mesenchymal Stem Cells (MSCs). Methods: Systematic Review by conducting literature searches using Google Scholar, PubMed, and Science Direct. The literature search method used PICO (Population, Intervention, Comparison, Outcome) is based on clinical trials in COVID-19 patients using experimental and observational research designs. Results: Based on four studies, 40 patient samples showed a proportion of 100% improvement in the lungs in patients who had complications of Acute Respiratory Distress Syndrome (ARDS) from increased serum cytokine IL-10, decreased IL-6, increased number of peripheral mononuclear cells, and decreased C-reactive protein. Conclusion: MSCs have an immunomodulating capacity to prevent cytokine storm processes in SARS-CoV-2 infection and improve lung organs in COVID-19 patients.